2017
DOI: 10.1007/s00442-017-3881-9
|View full text |Cite
|
Sign up to set email alerts
|

‘Trophic’ and ‘source’ amino acids in trophic estimation: a likely metabolic explanation

Abstract: Amino acid nitrogen isotopic analysis is a relatively new method for estimating trophic position. It uses the isotopic difference between an individual’s ‘trophic’ and ‘source’ amino acids to determine its trophic position. So far, there is no accepted explanation for the mechanism by which the isotopic signals in ‘trophic’ and ‘source’ amino acids arise. Yet without a metabolic understanding, the utility of nitrogen isotopic analyses as a method for probing trophic relations, at either bulk tissue or amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(174 citation statements)
references
References 112 publications
6
162
0
Order By: Relevance
“…, the algal and vascular plant primary producers were near the line where the TP Glu‐Phe values are equal to 1, with the corresponding β values. The precision levels (SD and potential uncertainty) of the TP Glu‐Phe of primary producers in this study are almost identical to the values that have been reported previously (Chikaraishi et al ; O'Connell ). Carnivorous fishes always lie at a higher position irrespective of the chosen β values.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…, the algal and vascular plant primary producers were near the line where the TP Glu‐Phe values are equal to 1, with the corresponding β values. The precision levels (SD and potential uncertainty) of the TP Glu‐Phe of primary producers in this study are almost identical to the values that have been reported previously (Chikaraishi et al ; O'Connell ). Carnivorous fishes always lie at a higher position irrespective of the chosen β values.…”
Section: Discussionsupporting
confidence: 90%
“…Compound‐specific isotope analysis of amino acids (CSIA‐AA) has been widely used to estimate the TP of organisms in the aquatic and terrestrial ecosystem because different amino acids record both the TP and nitrogen isotopic baseline information (Chikaraishi et al ; O'Connell ; Ohkouchi et al ). Differential 15 N enrichment levels between the two groups amino acids (i.e., the trophic and source groups) in single trophic stepwise represent the core of the CSIA‐AA approach and the study of trophic ecology (McClelland and Montoya ; Chikaraishi et al ).…”
Section: βCorr and The Contribution Of Vascular Plant As A Diet Resoumentioning
confidence: 99%
See 1 more Smart Citation
“…Results show it was possible to infer a recent drop in trophic level (rather than a change in nitrogen fixation) that may be attributable to industrial fishing. Amino‐acid‐specific δ 15 N analysis is an emerging field with its own methodological challenges (O'Connell, ), but one with considerable potential.…”
Section: Long‐term Changes In the Aquatic Environmentmentioning
confidence: 99%
“…Thus, source amino acids can be used to measure the δ 15 N values of primary producers, which is governed by regional patterns in nitrogen cycling processes (e.g., nitrogen fixation, denitrification, nitrification, nitrate assimilation). We can interpret ecological relationships using these basic patterns in amino acids, and with some consideration of the physiological and biochemical reactions that also influence isotope ratios …”
Section: Introductionmentioning
confidence: 99%